1997
DOI: 10.1002/(sici)1097-0215(19970529)71:5<838::aid-ijc23>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiogenesis inhibitor TNP-470 on the progression of human gastric cancer xenotransplanted into nude mice

Abstract: The effect of an angiogenesis inhibitor, TNP-470, on primary tumor growth, liver metastasis and peritoneal dissemination of gastric cancer was investigated by means of an orthotopic xenotransplanted model of 2 human gastric cancers, MT-2 and MT-5. TNP-470 showed a significant inhibitory effect on the growth of primary tumors after orthotopic transplantation of both xenografts when given at a dose of 30 mg/kg on alternate days from day 7 after transplantation (early treatment). However, growth of the MT-2 prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The predictive value of MVD has also been suggested in other studies in which a higher MVD was associated with the development of distant metastases (Tanigawa et al, 1996) or bone marrow micrometastases (Maehara et al, 1998). Similarly, experimental studies using antiangiogenic agents, such as TNP-470, have shown effectiveness in decreasing tumour proliferative activity and inhibiting the development of liver and peritoneal metastases (Kanai et al, 1997;Yoshikawa et al, 2000). These findings reinforce the relationship between tumour angiogenesis and the spread of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value of MVD has also been suggested in other studies in which a higher MVD was associated with the development of distant metastases (Tanigawa et al, 1996) or bone marrow micrometastases (Maehara et al, 1998). Similarly, experimental studies using antiangiogenic agents, such as TNP-470, have shown effectiveness in decreasing tumour proliferative activity and inhibiting the development of liver and peritoneal metastases (Kanai et al, 1997;Yoshikawa et al, 2000). These findings reinforce the relationship between tumour angiogenesis and the spread of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Test mice (n=4) were killed, and disseminated nodules on the mesentery were evaluated on the 28th day. In the TNP-short-treatment group, TNP-470 at 30 mg/kg was administered every other day beginning on day 14 and continuing through day 28, with the day of 1×10 7 PCI inoculation being day 0. Test mice (n=5) were killed and disseminated nodules on the mesentery were evaluated on the 28th day.…”
Section: Zymographic Detection Of Matrix Metalloproteinasesmentioning
confidence: 99%
“…However, its importance in the establishment and growth of peritoneal dissemination remains largely unknown, as very few studies have been conducted. 7) The peritoneal implants of pancreas adenocarcinoma patients are histologically composed of a proliferation of carcinoma cells accompanied by desmoplastic stromal reaction with neovascularization. Thus, inhibition of tumor angiogenesis might suppress peritoneal implants, as in the case of hematogenous metastatic nodules.…”
mentioning
confidence: 99%
“…We have previously reported the therapeutic effect of an angiogenesis inhibitor on the liver metastasis of human gastrointestinal malignancies. [4][5][6] In the present study, the therapeutic effect of vascular endothelial cell growth factor neutralizing monoclonal antibody (VEGFAb) on the liver metastasis of EN-1 was investigated by using a liver metastatic model, with the aim of developing a novel therapy for endocrine neoplasm. …”
mentioning
confidence: 99%